Synthesis of 2H-azirine-2,2-dicarboxylic acids and their derivatives - Anastasiya V. Agafonova; Mikhail S. Novikov; Alexander F. Khlebnikov (Beilstein Journal of Organic Chemistry)
Methods for the preparation of 3-aryl-2H-azirine-2,2-dicarboxylic acids and their amides, esters, and azides by FeCl2-catalyzed isomerization of 3-aryl-5-chloroisoxazole-4-carbonyl chlorides into 3-aryl-2H-azirine-2,2-dicarbonyl dichlorides followed by their reaction with nucleophiles are reported. Two approaches to the preparation of 3-aryl-5-chloroisoxazole-4-carbonyl chlorides have been developed.